Carriage of qnrA1 and qnrB2, blaCTX-M15, and complex class 1 integron in a clinical multiresistant Citrobacter freundii isolate - Ferreira, Sónia (2020)
A multiresistant Citrobacter freundii strain was recovered from a catheter from a patient hospitalized in Aveiro, Portugal. This strain harbored quinolone resistance genes, qnrA1 and qnrB2, both in a large plasmid.